A STUDY OF STUDENTS' PERCEPTION TOWARD MATHEMATICS, MATHEMATICS ANXIETY, MOTIVATION, AND ACHIEVEMENT IN MIDDLE SCHOOL - Mia Kusmiati, - (2012)
This research, entitled " A Study Of Students' Perception toward Mathematics, Mathematics Anxiety, Motivation, and Achievement in Middle School", is a research that is implemented in Pribadi Bilingual International School and SMPN 2 Cileunyi.This research is aimed to find relationship between students' perception toward mathematics, mathematics anxiety, motivation, and achievement. Also to find some causal of each variable. This research is conducting path analysis method. Population of this research is Bilingual International schools students and RSBI students in Bandung. Samples are 7th and 8th grade students of them. The students were given three kinds of questionnaire, they are perception questionnaire, mathematics anxiety questionnaire, and motivation questionnaire. The data is then being analyzed with students' mathematics achievement score using path analysis method.Findings of this research are that students' perception is 7,5% influencing to mathematics achievement, mathematics anxiety is 0,5% influencing to mathematics achievement, while motivation is 20,3% influencing to mathematics achievement. Perception is 29,9% influencing to motivation, mathematics anxiety is 6,0% influencing to motivation. The result showed that there are still many factors influencing mathematics achievement and each variable. Therefore it is necessary for the next researcher to study about them further.